Change yourself to change your institution: Perspectives on educational change (Scholars' Journal, 2020)
The main objective of this study is to discuss the perspectives of school change. This study is a theoretical analysis and based on document review. The concept of educational change is described as school improvement. It is one of the ways to address the changing social needs through the technological, political, and cultural change of the school. School improvement or change is to change the school system as a whole for the attainment of better results, but questions arise about how to change, who is to change, and what to change and answers are varied and complicated. The concept of educational change is multidimensional. The perspective of technological change focuses on well-equipped classrooms and the use of information communication technology. The perspective political change fosters on power, authority, and interests of people. The cultural viewpoint asserts that the values, norms, and behaviour influence the organizational performance and unless changing it, the system cannot be changed. School change is necessary for the Nepalese context and in doing so, all the three perspectives technological, political, and cultural are necessary to address. The technological part of the school system is nearly very poor, the party politics in schools is influencing the authority and the school culture is not favourable to address the changing needs of the society. So, all the dimensions are needed to be taken into consideration to change the school system in Nepal.